Biochemical and structural investigations of bothropstoxin-II, a myotoxic Asp49 phospholipase A2 from Bothrops jararacussu venom - Murakami, Mário T. [UNESP]; Lourenzoni, Marco R.; Arruda, Emerson Z.; Tomaz, Marcelo A.; Viçoti, Magno M. [UNESP]; Abrego, José R. B. [UNESP]; Melo, Paulo A.; Arni, Raghuvir K. [UNESP] (Bentham Science Publishers, 2008)
Bothropstoxin-II a calcium-dependent enzyme from Bothrops jararacussu venom causes tissue damage and several haemostatic disorders including platelet aggregation. In order to elucidate the structural determinants of its multiple pharmacological activities, we have studied the effects of suramin on Bothropstoxin-II and present details concerning the mode of binding. © 2008 Bentham Science Publishers Ltd.
Keywords: Pharmacological activities; Phospholipases A2; Structural studies; Suramin